Conscious Business in Germany Assessing the Current Situation and Creating an Outlook for a New Paradigm - Stahlhofer, Nicolas Josef (CSR, Sustainability, Ethics & Governance,, 2018)
This book presents conscious business as a constantly expanding and powerful approach to reinvent and shape organizations in a human and beneficial manner. In particular it examines the core characteristics, main drivers and challenges of conscious businesses in Germany. The book offers a structured overview of the current situation of the concept and outlines important issues that need to be considered in order to make independent decisions. Four case studies of successful conscious companies - differing in terms of their size, industry, legal form and international orientation - reveal concrete best practices and provide evidence for the approach's ability to deliver business paradigms that are simultaneously purposeful and profitable.